(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2014)
The present study was designed to get preliminary idea about the pharmacokinetic behavior of the Bangladeshi population through estimating plasma amoxicillin concentration by High-Performance Liquid Chromatography (HPLC) with ultraviolet detection. In this study, Bangladeshi healthy volunteers were divided in two groups, 8 Bangladeshi Bangalee and 7 Bangladeshi Tribal male healthy volunteers. Both the groups received 500 mg of amoxicillin in oral route and blood samples were collected at 0, 30, 60, 120, 180, 360 and 480 minutes after drug administration. After 1 week of washout period, same volunteers of two groups received 500 mg of amoxicillin in intravenous route. In case of oral route, the Cmax, AUC08h, Tmax and T1/2 values for Bangladeshi Bangalee and Tribal healthy volunteers were 6.78 ± 1.20 & 9.10 ± 1.34 ìg/mL, 1290.13 ± 158.39 & 1766.06 ± 188.37 ìg min/mL, 82.50 ± 32.05 & 102.86 ± 29.28 min and 96.05 ± 3.80 & 88.15 ± 5.33 min respectively. The difference in Cmax, AUC08h and T1/2 values between these two groups of volunteers was significant (p<0.01, p<0.001 and p<0.01 respectively). However, the difference in Tmax was not significant (p>0.05). In case of intravenous route, the C30 min and AUC08h values for Bangladeshi Bangalee and Tribal healthy volunteers were 17.88 ± 1.14 & 18.58 ± 0.71 ìg/mL, 2297.96 ± 222.49 & 2376.41 ± 149.99 ìg min/mL respectively and the difference was not significant (p>0.05). The T1/2 for Bangladeshi Bangalee and Tribal healthy volunteers were 97.50 ± 3.33 & 94.40 ± 2.33 min respectively and the difference was significant (p<0.05). The Mean Percent Absolute Bioavailability in Bangladeshi Bangalee and Tribal healthy volunteers was 56.76 ± 5.39 and 74.17 ± 3.90 respectively and the difference was highly significant (p<0.001). The study concluded that the pharmacokinetic parameters of amoxicillin significantly varied among Bangladeshi Bangalee and Bangladeshi Tribal healthy volunteers indicating necessity of further study on population pharmacokinetic to formulate tailor-made drug therapy in these groups of people. http://dx.doi.org/10.3329/bjpp.v26i1-2.19958 Bangladesh J Physiol Pharmacol 2010; 26(1&2) : 1-9